Constitutional Limits to Administration Authority in Light of the Corona Pandemic: A Comparative Analytical Study - Soz Hameed Majeed (QALAAI ZANIST JOURNAL, 2021)
Since the beginning of 2021, the Corona virus, which causes 19-COVID-19 disease, has affected public life and private law areas, which became different with the difference in the authority of administration during the organization of the pandemic, as it expanded to Tamer by closing other whole and partial times, as well as other Factors of social distancing and other legal repercussions that affect the rights and freedoms of society. Certain procedures in cases of crises and disasters, and the initiation of certain procedures to preserve the security and safety of society, and the initiation of crises in crises that all local communities put pressure on, without prejudice to the tenets, principles and provisions contained in the Algerian constitution.